Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445403
|View full text |Cite
|
Sign up to set email alerts
|

”Beyond 3D printers”: Understanding Long-Term Digital Fabrication Practices for the Education of Visually Impaired or Blind Youth

Abstract: Fig. 1. Although digital fabrication did not replace traditional techniques for producing accessible tactile media, laser cutting was promptly adopted for creating educational tools and accessories such as [a] this conversion table with braille cubes, replacing some tactile transcription and this accessible square; or [b] representations of concepts with rich textures, here a puzzle circulatory system. 3D printing has a narrower range of applications: while professionals adopt it for some manipulable represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The results of our study show that the limited number of 3D printers in schools and the limited access of teachers and students to this teaching tool also significantly affect its applicability in the classroom. The lack of 3D printers in schools as a limiting factor for the application of this technology in the classroom has been cited in previous research as a major limiting factor for the use of this educational technology in developed countries such as the United States (Brulé & Bailly, 2021). Considering that the availability of technology is one of the basic requirements for its use in education, the data obtained in our research that teachers believe four to five 3D printers to be a desirable number for successful implementation is very important for future schools equipped with this educational technology.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study show that the limited number of 3D printers in schools and the limited access of teachers and students to this teaching tool also significantly affect its applicability in the classroom. The lack of 3D printers in schools as a limiting factor for the application of this technology in the classroom has been cited in previous research as a major limiting factor for the use of this educational technology in developed countries such as the United States (Brulé & Bailly, 2021). Considering that the availability of technology is one of the basic requirements for its use in education, the data obtained in our research that teachers believe four to five 3D printers to be a desirable number for successful implementation is very important for future schools equipped with this educational technology.…”
Section: Discussionmentioning
confidence: 99%
“…The results are also in line with [35] where six out of seven OMIs were interested in creating and using 3D objects. In general, concerns about DIY techniques were raised by professionals of disability in several studies [17,60,63]. Vandenberghe et al, investigated maker technologies for empowering occupational therapists and they claim that infrastructural changes (funding, availability of professionals, etc.)…”
Section: Making Of 3d Interactive Modelsmentioning
confidence: 99%
“…Almost half of the research papers (47%) included in the review are focused on PVIs, meaning that the implementation of good practices and methods can empower OMIs and PVIs. For example, Brulé et al, in a long-term study, showed that low-vision professionals actually use laser cutters and judge them as versatile and flexible tools [17]. In conclusion, it seems that 3D printing and laser cutting are complementary techniques that professionals will be able to rely on in the near future.…”
Section: Making Of 3d Interactive Modelsmentioning
confidence: 99%
“…I stayed for eighteen months for field work and continued doing interviews and collecting their documentation of their making practices for four more years. Throughout, I was involved in making myself, focusing especially on more complex three-dimensional representations used in classrooms, for instance tactile globes and models of insects (Brulé and Bailly 2021).…”
Section: A History Of Makingmentioning
confidence: 99%
“…For more complex shapes, a model could include a part based on a 3D scan. This is the approach used in GripFab, a design tool for occupational therapists to create custom grips for everyday objects (Buehler et al 2014). In contrast, previous methods of automation have relied on a range of standardized sizes, necessary to create the molds for plastic, or other industrial fabrication processes.…”
Section: The Objects Of Makingmentioning
confidence: 99%